Prevalence and characterization of piperaquine, mefloquine and artemisinin derivatives triple-resistant Plasmodium falciparum in Cambodia. (12th December 2022) - Mairet-Khedim, Mélissa; Roesch, Camille; Khim, Nimol; Srun, Sreynet; Bouillon, Anthony; Kim, Saorin; Ke, Sopheakvatey; Kauy, Chhayleang; Kloeung, Nimol; Eam, Rotha; Khean, Chanra; Kul, Chanvong; et al.
Abstract: Background: In early 2016, in Preah Vihear, Northern Cambodia, artesunate/mefloquine was used to cope with dihydroartemisinin/piperaquine-resistant Plasmodium falciparum parasites. Following this policy, P. falciparum strains harbouring molecular markers associated with artemisinin, piperaquine and mefloquine resistance have emerged. However, the lack of a viable alternative led Cambodia to adopt artesunate/mefloquine countrywide, raising concerns about a surge of triple-resistant P. falciparum strains. Objectives: To assess the prevalence of triple-resistant parasites after artesunate/mefloquine implementation countrywide in Cambodia and to characterize their phenotype. Methods: For this multicentric study, 846 samples were collected from 2016 to 2019. Genotyping of molecular markers associated with artemisinin, piperaquine and mefloquine resistance was coupled with phenotypic analyses. Results: Only four triple-resistant P. falciparum isolates (0.47%) were identified during the study period. These parasites combined the pfk13 polymorphism with pfmdr1 amplification, pfpm2 amplification and/or pfcrt mutations. They showed significantly higher tolerance to artemisinin, piperaquine and mefloquine and also to the mefloquine and piperaquine combination. Conclusions: The use of artesunate/mefloquine countrywide in Cambodia has not led to a massive increase of triple-resistant P. falciparum parasites. However, these parasites circulate in the population, and exhibit clear resistance to piperaquine, mefloquine and their combination in vitro . This study demonstrates that P. falciparum can adapt to more complex drug associations, which should be considered in future therapeutic designs.